Effective removal of Cr(VI) in aqueous solutions using Caulis lonicerae residue fermented by Phanerochaete chrysosporium. Issue 9 (1st October 2021) - Tao, Fengyun; Wang, Yue; Zhao, Zhanhong; Liu, Xiaojing; Zhang, Gaoyu; Li, Chi; Wang, Zhaoxuan; Huo, Qing
Abstract: Cr(VI) is one of the most common environmental pollutants. The non-biodegradable Cr(VI) in aqueous solution accumulates along the food chain and damages the health of plant, animal, and human. In this study, solid-state fermentation technology was used to treat Caulis lonicerae residue to improve its adsorption capacity for Cr(VI). Caulis lonicerae can be used to extract the active ingredients such as organic acids, flavonoids, and triterpenoid saponins that have various effects including anti-oxidation and immune boosting. However, there is no proper treatment for large amount of residue left after extraction. The Phanerochaete chrysosporium was inoculated into the residue for solid-state fermentation, and the adsorption capacity of C. lonicerae residue before (CLr) and after fermentation (FCLr) regarding Cr(VI) adsorption was compared. In the range of 40–120 mg/L Cr(VI), the adsorption capacity of FCLr was significantly higher than that of CLr. The scanning electron microscopy (SEM) results exhibited a rougher surface of FCLr. The Fourier-transform infrared spectroscopy (FTIR) results revealed that the structure of FCLr was affected by the combination of Cr(VI), and the multiple functional groups interacted with Cr(VI) (such as –OH, C–H, C = O, C–O–C, and C–O). The adsorption capacity could reach 48.91 mg/g and the Cr(VI) removal percentage may reach 98.07% for FCLr increased by 28.24% through fermentation.